Differential response rates to irradiation among patients with human papillomavirus positive and negative oropharyngeal cancer1. (24th September 2012) - Chen, Allen M.; Li, Judy; Beckett, Laurel A.; Zhara, Talia; Farwell, Gregory; Lau, Derick H.; Gandour‐Edwards, Regina; Vaughan, Andrew T.; Purdy, James A.
Abstract Objectives/Hypothesis: To evaluate the responsiveness of human papillomavirus (HPV) ‐positive and HPV‐negative oropharyngeal cancer to intensity‐modulated radiotherapy (IMRT), using axial imaging obtained daily during the course of image‐guided radiotherapy (IGRT). Study Design: Observational cohort study with matched‐pair analysis of patients irradiated for HPV‐positive and HPV‐negative oropharygeal cancer. Methods and Materials: Ten patients treated by IMRT to 70 Gy for locally advanced, HPV‐positive squamous cell carcinoma of the oropharynx were matched to one HPV‐negative control subject by age, gender, performance status, T‐category, tumor location, and the use of concurrent chemotherapy. The gross tumor volume (GTV) was delineated on daily IGRT scans obtained via kilovoltage cone‐beam computed tomography (CBCT). Mathematical modeling using fitted mixed‐effects repeated measure analysis was performed to quantitatively and descriptively assess the trajectory of tumor regression. Results: Patients with HPV‐positive tumors experienced a more rapid rate of tumor regression between day 1 of IMRT and the beginning of week 2 (−33% Δ GTV) compared to their counterparts with HPV‐negative tumors (−10% Δ GTV), which was statistically significant (p<0.001). During this initial period, the average absolute change in GTV was −22.9 cc/week for HPV‐positive tumors and −5.9 cc/week for HPV‐negative tumors (p<0.001). After week 2 of IMRT, the rates of GTV regression were comparable between the two groups. Conclusions: HPV‐positive oropharyngeal cancers exhibited an enhanced response to radiation, characterized by a dramatically more rapid initial regression than those with HPV‐negative tumors. Implications for treatment de‐intensification in the context of future clinical trials and the possible mechanisms underlying this increased radiosensitivity will be discussed. Laryngoscope, 2013